Relationship between the Competitive Strategies and Supply Chain Management of Financial Companies for Securities - Abed Mohammad, Raheem; Ali Balchat, Baqer; Shujairi, Rifaatibrahimkhudhair (ExcelingTech, 2019)
Competitive strategies are essentially designed to exploit the competitive advantage of the organization. The competitive strategy is in business practices to attract customers by meeting their expectations, facing competitive pressures and enhancing market positioning. It is noted that the choice of competitive strategy and supply chain management affects the performance of the company, whether financial or non-financial and that the Iraqi financial system consists of a wide range of institutions that have been listed in the Iraqi market for securities.In the fierce market competition, the transformation of market competition based on price and quality of the original product competition gradually shifts to the time of the supply chain competition, which makes scholars begin to study the supply chain based on time competition and enterprises especially in automobile industry begin to explore suitable time-based supply chain. The aim of this study is to assess the relationship between the performance of the financial sector companies listed in the Iraqi market for securities and the supply chain impacts on competitive strategies adopted in the last three years. A questionnaire was the main tool used to collect primary data while secondary data were used to supplement the main tool and the results were analyzed using regression analysis. The study found that companies have improved along organizational performance requirements measured across different indicators.Performance has been guided by both financial and non-financial performance measures. The study concluded that the performance was determined to some extent by different strategies adopted by each firm in its operations over the past three years and that there was no specific single strategy, but was often a combination of many competitive strategies. The study recommends expanding its market coverage with different products. It is also recommended that the government also protects the financial sector companies listed in the national labor market from intense competition from international companies through international policies.